Introducing Christian Doctrine - Erickson, Millard J.; Hustad, L. Arnold (Grand Rapids, Mich. : Baker Academic, 2001)
Presents a comprehensive introduction to Christian doctrine and includes discussions on topics such as punishment for sin, various concepts of salvation, and the humanity of Jesus Christ.
[Part VII.] The person of Christ -- The deity of Christ -- The humanity of Christ -- The unity of the person of Christ -- [Part VIII.] The work of Christ -- Introduction to the work of Christ -- The central theme of atonement -- [Part IX.] The Holy Spirit -- The person of the Holy Spirit -- The work of the Holy Spirit -- [Part X.] Salvation -- Conceptions of salvation -- The antecedent to salvation: predestination -- The beginning of salvation: subjective aspects -- The beginning of salvation: objective aspects -- The continuation and completion of salvation -- [Part XI.] The church -- The nature of the church -- The role and government of the church -- The ordinances of the church -- [Part XII.] The last things -- Introductory matters and individual eschatology -- The second coming and its consequences -- Millenial and tribulational views -- Final states.
Includes bibliographical references and indexes.
Keywords: Theology, Doctrinal